2016
DOI: 10.1002/mbo3.350
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mycobacterium avium subsp. paratuberculosis load in raw bulk tank milk in Emilia‐Romagna Region (Italy) by qPCR

Abstract: Consumption of milk and dairy products is considered one of the main routes of human exposure to Mycobacterium avium subsp. paratuberculosis (MAP). Quantitative data on MAP load in raw cows’ milk are essential starting point for exposure assessment. Our study provides this information on a regional scale, estimating the load of MAP in bulk tank milk (BTM) produced in Emilia‐Romagna region (Italy). The survey was carried out on 2934 BTM samples (88.6% of the farms herein present) using two different target sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Sung and Collins (1998) have suggested that a MAP concentration of 10 6 cfu/mL should be used when modelling MAP destruction for safety reasons. This is high, and the more conservative figure of 10 4 cfu/mL, which is still high, as suggested by Grant et al (1999) would appear to be justified from the work of Ricchi et al (2016) as a worst-case scenario. The number of microbial survivors, N2, following the heat treatment of a microbial population, N1, at a defined temperature for a time, T, can be calculated using Eqn 1 (Stumbo 1973) providing the D-value of the organism is known.…”
Section: Calculation Of the Number Of Log Reductions Of Map Followingmentioning
confidence: 86%
“…Sung and Collins (1998) have suggested that a MAP concentration of 10 6 cfu/mL should be used when modelling MAP destruction for safety reasons. This is high, and the more conservative figure of 10 4 cfu/mL, which is still high, as suggested by Grant et al (1999) would appear to be justified from the work of Ricchi et al (2016) as a worst-case scenario. The number of microbial survivors, N2, following the heat treatment of a microbial population, N1, at a defined temperature for a time, T, can be calculated using Eqn 1 (Stumbo 1973) providing the D-value of the organism is known.…”
Section: Calculation Of the Number Of Log Reductions Of Map Followingmentioning
confidence: 86%
“…Previous comparative studies of qPCR and conventional culture have demonstrated good correlation in high sample loads present in feces (Douarre et al, 2010; Mita et al, 2016) but the inability of conventional culture methods to accurately culture low loads of viable organisms from clinical samples introduces problems. Culture sensitivity for MAP has only ever been as good as 2–3 log 10 (Ricchi et al, 2016), thus at low loads correlations to DNA presence are difficult to obtain and the true relationship between genome equivalent values and the demonstrable viable MAP count in these samples remains uncertain (Kralik et al, 2012; Plain et al, 2015). The underlying reasons for these discrepancies are probably multi-variant.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MAP to exist in a variety of phenotypes, some with a high resistance to killing (Grant and Rowe, 2004), has increased the importance of providing accurate quantitative estimates of viable counts when testing for the presence of this pathogen in food (Botsaris et al, 2016; Galiero et al, 2016; Ricchi et al, 2016), animal and human samples (Timms et al, 2016). MAP is widely accepted as a difficult organism to culture reproducibly and accurately, particularly at low loads (Hines et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Here, an amount of 15 CFU per ml was detected with IS 900 in a qPCR and 200 CFU per ml with f 57 in a qPCR (Ricchi et al . ). Due to the results of the LOD of MAP in LAMP, compared to those in the qPCR shows, that ISM ap02 is a trustworthy target gene with a high sensitivity level.…”
Section: Discussionmentioning
confidence: 97%
“…Losing one potency step compared to feces testing milk is not unusual (Ricchi et al . ). With this in mind we especially concentrated on the cream layer to not miss MAP bacteria.…”
Section: Discussionmentioning
confidence: 97%